Utilization Of Healthcare Services To General Patient At Inpatient Unit of Anutapura General Hospital, Palu City - Fausiah, Fausiah (Tadulako University, 2019)
The number of inpatient visits in RSU Anutapura Palu, where in 2015 inpatient visits of 5,640, then in 2016 patient visits decreased to 5,451, in 2017 also decreased to 3,999 and in 2018 also decreased Drastic to 1,146 patient visits. This research aims to determine the utilization of health services in patients in general hospitalization in RSU Anutapura Palu. This type of research is quantitative descriptive. Research was conducted from May-June 2019. The population in the study is a visitor (number of hospitalizations) at the General Hospital (RSU) Anutapura Palu. In this case the people who use health services in the General Hospital (RSU) Anutapura Palu recorded as many as 1,146 visitors (patients) in the year 2018. Primary data collection is through questionnaires and secondary data through the study of patient record documents and other supporting documents. The utilization of health services in patients in general hospitalization in RSU Anutapura Palu is well from the aspects of health beliefs, abilities and needs. RSU Anutapura Palu is expected to be able to improve the promotion of health services so that people use the health services provided. Â